Relations between background (Searle) and the theory of mind (Rivière) (2019)
This text aims to show possible relationships between the theory of mind proposed by Angel Rivière, and the concept of Background, raised in the philosophy of the mind by John Searle. It starts with an overview of the theory of mind and some of their frames of explanation in cognitive psychology. The concept of Background, and finally some arguments that support the way in which the theory of mind might be conceived as a background capacity are also explained. The main conclusion consists in stating that both theory of the mind and background ability refer to types of knowledge, which constitute themselves in conditions of possibility for individuals’ mental life, and for the relationship with the other.